1998
DOI: 10.1038/sj.ejcn.1600591
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in vitamin D status and calcium absorption do not influence bone turnover in young women

Abstract: Objective: To evaluate the effect of seasonal variations in UV B-exposure on calcium absorption and bone turnover in young women with the overall goal to assess the potential bene®t of a vitamin D supplementation during wintertime. Design: Cross-sectional study. Setting: Area of Bonn, Germany (51 N). Subjects: Thirty-eight women (24.5 AE 0.5 y) studied in winter and 38 females of the same age (24.7 AE 0.4 y) studied in summer. Results: As estimated by a 4 d food record, both groups had similar dietary calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 40 publications
7
39
2
Order By: Relevance
“…A study conducted in postmenopausal women corroborates these findings, reporting no correlation between 25(OH)D and PTH at physiological concentrations (Villareal et al, 1991). Vitamin D only plays a role in the synthesis of PTH, whereas the secretion of the hormone is regulated primarily by calcium (Pepe et al, 2005;Zittermann et al, 1998). We speculate that no change in PTH concentrations was observed in this study as subjects had adequate dietary intakes of calcium, before supplementation with another 1500 mg calcium/day and were not severely deficient in vitamin D.…”
Section: Discussionmentioning
confidence: 82%
“…A study conducted in postmenopausal women corroborates these findings, reporting no correlation between 25(OH)D and PTH at physiological concentrations (Villareal et al, 1991). Vitamin D only plays a role in the synthesis of PTH, whereas the secretion of the hormone is regulated primarily by calcium (Pepe et al, 2005;Zittermann et al, 1998). We speculate that no change in PTH concentrations was observed in this study as subjects had adequate dietary intakes of calcium, before supplementation with another 1500 mg calcium/day and were not severely deficient in vitamin D.…”
Section: Discussionmentioning
confidence: 82%
“…Biochemical and hormonal markers of bone metabolism vary significantly (P < 0·05) according to the season, consistent with an acceleration of bone turnover and possible subclinical vitamin D deficiency in winter (Woitge et al 1998). In young women a reduction in serum 25-OHD was associated with decreased intestinal Ca and P absorption during wintertime, but was not associated with the changes in bone turnover markers (serum carboxy-terminal propeptide of type I procollagen (PICP) and urinary deoxypyridinoline; Zittermann et al 1998). …”
Section: Seasonmentioning
confidence: 90%
“…However, earlier results have also demonstrated that a rise in serum 25(OH)D from 30 to 70 nmol/l had no beneficial effects on biomarkers of bone metabolism if subjects had a recommended daily calcium intake. In this case, the surplus of absorbed calcium was at least in part excreted in the urine (Zittermann et al, 1998). Since both, an increase in oral calcium intake and higher serum 25(OH)D levels result in a rise of intestinal absorbed calcium, calcium and vitamin D can obviously replace each other relative to their effects on calcium supply and calcium-mediated bone turnover.…”
Section: Resultsmentioning
confidence: 94%